AtaT Improves the Stability of Pore-Forming Protein EspB by Acetylating Lysine 206 to Enhance Strain Virulence - He, Zhili; Li, Tao; Wang, Jianxin; Luo, Deyan; Ning, Nianzhi; Li, Zhan; Chen, Fanghong; Wang, Hui (Frontiers in Microbiology, 2021)
A novel type II toxin of toxin-antitoxin system (TAs), Gcn5-related N-acetyltransferase (GNAT) family, was reported recently. GNAT toxins are mainly present in pathogenic species, but studies of their involvement in pathogenicity are rare. This study discovered that the GANT toxin AtaT in enterohemorrhagic Escherichia coli (EHEC) can significantly enhance strain pathogenicity. First, we detected the virulence of ΔataT and ΔataR in cell and animal models. In the absence of ataT, strains showed a lower adhesion number and host cells presented weaker attaching and effacing lesions, inflammatory response, and pathological injury. Next, we screened the acetylation substrate of AtaT to understand the underlying mechanism. Results showed that Escherichia coli pore-forming protein EspB, which acts as a translocon in type III secretion system(T3SS) in strains, can be acetylated specifically by AtaT. The acetylation of K206 in EspB increases protein stability, and maintains the efficiency of effectors translocating into host cells to cause close adhesion and tissue damage.